The Dziani Dzaha Lake: A long‐awaited modern analogue for superheavy pyrites. Issue 3 (22nd January 2022) - Cadeau, Pierre; Cartigny, Pierre; Thomazo, Christophe; Jézéquel, Didier; Leboulanger, Christophe; Sarazin, Gérard; Ader, Magali
Abstract: Sedimentary records of superheavy pyrites in Phanerozoic and Proterozoic successions (i.e., extremely positive δ 34 Spyrite values together with higher δ 34 Spyrite than coeval δ 34 SCAS ) are mostly interpreted as resulting either from secondary postdepositional processes or from multiple redox reactions between sulfate and sulfide in stratified sulfate‐poor environments. We report here the first observation of strongly positive δ 34 S values for both dissolved sulfate and sulfide (average δ 34 Sdiss.sulfate value of 34.6‰ and δ 34 Sdiss.sulfide values of 36.7‰) compared to the present‐day seawater δ 34 Sdiss .sulfate ( 21‰), with a negative apparent fractionation between sulfate and sulfide (∆ 34 Sdiss.sulfate‐diss.sulfide −2.1 ± 1.4‰), in the sulfate‐poor (<3 mm ) modern thalassohaline lacustrine system Dziani Dzaha (Mayotte, Indian Ocean). Overall, surface sediments faithfully record the water column isotopic signatures including a mainly negative ∆ 34 Ssed.sulfate‐sed.sulfide (−4.98 ± 4.5‰), corresponding to the definition of superheavy pyrite documented in the rock record. We propose that in the Dziani Dzaha this superheavy pyrite signature results from a two‐stage evolution of the sulfur biogeochemical cycle. In a first stage, the sulfur cycle would have been dominated by sulfate from initially sulfate‐rich marine waters. Overtime, Raleigh distillation by microbial sulfate reduction coupled with sulfide burial in the sediment would have progressively enriched in 34 S the water column residual sulfate. In a second still active stage, quantitative sulfate reduction not only occurs below the halocline during stratified periods but also in the whole water column during fully anoxic episodes. Sulfates are then regenerated by partial oxidation of sulfides as the oxic–anoxic interface moves downward. These results demonstrate that the atypical superheavy pyrite isotope signature does not necessarily require postdepositional or secondary oxidative processes and can result from primary processes in restricted sulfate‐poor and highly productive environments analogous to the Dziani Dzaha.